PERUMUSAN STRATEGI PEMASARAN WEDANG SECANG INSTAN “MAGNOER” DENGAN PENDEKATAN SOAR - Rahmah, Rasya Aulia; A'yuni, Nur Rohmah Lufti; Nalinda, Rika (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
This study aims to formulate a marketing strategy for the product "Magnoer" Instant Secang Herbal Drink produced by Taruna Agro Nusantara MSME using the SOAR (Strengths, Opportunities, Aspirations, and Results) analysis method. The SOAR approach was selected for its emphasis on leveraging internal strengths and external opportunities to achieve strategic growth and business aspirations. Data were collected through interviews, focus group discussions (FGD), and questionnaires involving 100 respondents, determined using the Lemeshow formula. The findings revealed key internal strengths such as high-quality raw materials, PIRT certification, and affordable pricing. External opportunities included the growing trend of a healthy lifestyle and the strategic location of Yogyakarta as a tourist destination. The resulting strategies include building strong product branding, developing innovative products, expanding distribution channels, and utilizing digital marketing. The IE matrix analysis placed the company in quadrant I, indicating a need for a “grow and build” strategy. By implementing the SOAR-based strategy, the MSME is expected to enhance competitiveness and sustainably expand its market.